RNA-seq Insights Into the Impact of Alteromonas macleodii on Isochrysis galbana - Cao, Jia-Yi; Wang, Ying-Ying; Wu, Min-Nan; Kong, Zhou-Yan; Lin, Jing-Hao; Ling, Ting; Xu, Si-Min; Ma, Shuo-Nan; Zhang, Lin; Zhou, Cheng-Xu; Yan, Xiao-Jun; Xu, Ji-Lin (Frontiers in Microbiology, 2021)
Phycospheric bacteria may be the key biological factors affecting the growth of algae. However, the studies about interaction between Isochrysis galbana and its phycospheric bacteria are limited. Here, we show that a marine heterotrophic bacterium, Alteromonas macleodii, enhanced the growth of I. galbana, and inhibited non-photochemical quenching (NPQ) and superoxide dismutase (SOD) activities of this microalgae. Further, we explored this phenomenon via examining how the entire transcriptomes of I. galbana changed when it was co-cultured with A. macleodii. Notable increase was observed in transcripts related to photosynthesis, carbon fixation, oxidative phosphorylation, ribosomal proteins, biosynthetic enzymes, and transport processes of I. galbana in the presence of A. macleodii, suggesting the introduction of the bacterium might have introduced increased production and transport of carbon compounds and other types of biomolecules. Besides, the transcriptome changed largely corresponded to reduced stress conditions for I. galbana, as inferred from the depletion of transcripts encoding DNA repair enzymes, superoxide dismutase (SOD) and other stress-response proteins. Taken together, the presence of A. macleodii mainly enhanced photosynthesis and biosynthesis of I. galbana and protected it from stress, especially oxidative stress. Transfer of fixed organic carbon, but perhaps other types of biomolecules, between the autotroph and the heterotroph might happen in I. galbana-A. macleodii co-culture. The present work provides novel insights into the transcriptional consequences of I. galbana of mutualism with its heterotrophic bacterial partner, and mutually beneficial associations existing in I. galbana-A. macleodii might be explored to improve productivity and sustainability of aquaculture algal rearing systems.